2006
DOI: 10.14238/pi41.4.2001.202-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of epilepsy among patients with cerebral palsy

Abstract: Epilepsy is a chronic condition due to cerebral function disorders. Epilepsy occurs as a common complication of many neurological disorders such as cerebral palsy (CP) that can affect further brain damage especially if they are with prolonged seizure. The incidence of epilepsy among patients with CP varies between 25-35%. The high incidence of epilepsy among patients with CP suggests that this disorder has common or related origins. We carried out the retrospective study to determine incidence of epilepsy amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
1
0
5
Order By: Relevance
“…Previous studies also found the spastic quadriplegia as the most common type of CP found. 7,10,14 There were 92 of 236 (39%) spastic CP subjects who had epilepsy. This result was similar to the result found by Kulak et al who found 76 of 172 (44.2%) spastic CP children in their study suffered from epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also found the spastic quadriplegia as the most common type of CP found. 7,10,14 There were 92 of 236 (39%) spastic CP subjects who had epilepsy. This result was similar to the result found by Kulak et al who found 76 of 172 (44.2%) spastic CP children in their study suffered from epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Kajian literatur mendapatkan bahwa anak dengan palsi serebral (PS) sering disertai beberapa penyakit penyerta di antaranya epilepsi. 18,19,20 Prevalens epilepsi pada anak dengan PS sekitar 15%-55%. Peet, 21 menemukan 62/145 (43%) kasus epilepsi di sekolah anak-anak yang berkebutuhan khusus.…”
Section: Pembahasanunclassified
“…Pada anak dengan palsi serebral terdapat peningkatan risiko terjadinya epilepsi, 1 Surveillance of Cerebral Palsy in Europe (SCPE) melaporkan 35% anak palsi serebral menderita epilepsi, 6 Paucic-Kirincic et al 35,9%, 7 Kwong et al 37,6%, 8 Sianturi et al 37,3%, 9 dan Rahmat et al 39%. 10 Asfiksia neonatal dapat mengakibatkan terjadinya palsi serebral, dan epilepsi bila mengenai area tertentu seperti korteks serebri atau lobus temporal.…”
Section: -5unclassified
“…10 Tipe epilepsi yang sering ditemukan pada palsi serebral yaitu epilepsi umum tonik-klonik dan parsial. 7,9,10 Manifestasi klinis epilepsi pada palsi serebral tergantung dari letak dan luas kerusakan otak.…”
Section: 9unclassified